Automation of the control processes of the refrigeration units condensers - Bukaros, Valeriya Mykolayevna; Onishchenko, Oleg Anatolyevych; Naleva, Galyna Vasylivna; Bukaros, Andrii Yuriyovych (НТУ "ХПІ", 2017)
In the article energy efficient ways of the condensing pressure (temperature) control in refrigeration units for various purposes are considered. The comparative analysis of the circuit solutions of the condensing temperature regulators for air cooling condensers is conducted with simulation methods. Modeling of the single-phase system of the regulator pulse-phase control triac HPC1/4 showed that this system has a low power factor. The feasibility of the condensing temperature regulators implementation on the basis of the three-phase frequency converter with DC chain is substantiated for the low and medium cooling capacity refrigeration units. The disadvantages of the existing systems of the condensing pressure stabilization of the refrigeration units water cooling condensers are highlighted. The research of two proposed control systems of the water-cooled condensers of the medium and high cooling capacity refrigeration units is conducted. It is established that the using of the principles of partial invariance to main disturbances with elements of the nonlinear correction can improve the energy efficiency of refrigeration units. Also it is provided by modeling the processes in the shell and tube capacitor KTP-300 of the ship refrigeration unit that the using of variable structure systems further improves the dynamic quality of control processes with large fluctuations of the heat loads.

Методами імітаційного моделювання проведений порівняльний аналіз схемотехнічних рішень регуляторів температури конденсації. Обґрунтовано доцільність реалізації таких регуляторів на базі трифазного перетворювача частоти з ланкою постійного струму. Проведено дослідження двох систем керування охолодженням водяних конденсаторів холодильних установок. Доведено, що використання запропонованих алгоритмів управління дозволить підвищити енергетичну ефективність холодильних установок і якість динамічних процесів управління при значних коливаннях теплових навантажень.
Автоматизація процесів керування конденсаторами холодильних установок
Keywords: condensing pressure; condensing temperature regulator; control system; тиск конденсації; регулятор температури конденсації; система керування